Effects of landscape environmental settings on microclimate in enhancing pedestrian walking distance in tropical campus environment - Kasim, Zanariah (2019)
Design is one of the primary elements in conceptualizing campus conducive for learning. One of the criteria that define such as a campus is the promotion of greens, open spaces and walkways. Walkways are important as it helps to create a conducive and healthy campus. An environment with comfortable walkways tends to entice walking. Walking contributes to health and a sustainable way of transportation around campus. Nevertheless, a tropical climate has high ambient air temperatures and relative humidity year-round making walking uncomfortable and unpopular. A suitable microclimate can provide thermal ameliorating effects on pedestrians. However, how it affects pedestrian walking distance and the landscape environmental settings have not been adequately investigated. A good knowledge on campus microclimates becomes important in sustainable campus planning and design. Therefore, this research investigated pedestrians’ thermal comfort and comfortable walking distances for different landscape settings in a tropical campus pedestrian environment. It observes and measures pedestrian thermal comfort and walking distance based principally on the physical properties of the landscape settings and the surrounding environment.